Solvent-free multicomponent synthesis of 2-arylpyridines using p-sulfonic acid calix[6]arene as reusable catalyst - Sathicq, Angel Gabriel (2015)
An new and efficient methodology for obtaining 2-arylpyrimidines based on the use of psulfonic acid calix[6]arene as organocatalyst is proposed. The methodology involves the formation of 1,2-dihydropyridine intermediates using a variety of aromatic aldehydes with methyl or ethyl acetoacetate and ammonium acetate, which are the same starting materials as in the Hantzsch reaction, under solvent-free reaction conditions, at 25 ºC, followed by air oxidation for 12 h. The catalyst efficiency is not compromised after its successive use in reactions. Eleven examples were obtained with very good to excellent yields of 2-arylpyridines (92%-62%). This is the first report about the use of calixarenes as catalyst in the multicomponent synthesis of 2-arylpyridines (molecules with biological activity potential)